Subordinative Construction of Tamiang Malay Language: Syntactic Typology Study - Ningrum, Dwi Kurnia Surya; Suryani, Siti (International Journal Linguistics of Sumatra and Malay, 2023)
This study aims to identify the syntactic typology of Tamiang Malay, focusing specifically on the co-referential patterns of grammatical relations to its arguments, including S, A and P in subordinative construction. This research is qualitative research. This study used a descriptive research design to investigate the syntactic typology of Tamiang Malay language. Data collection was conducted through a fieldwork in Tamiang Malay-speaking communities in Batu Lapan Sub-Village, Rantau Sub-District, Rantau Pauh Village, Aceh Tamiang District, Aceh Province, Indonesia. Tamiang Malay exhibits a unique syntactic structure that combines different types of clauses, including intransitive and transitive clause. The findings demonstrate the existence of several co-referential patterns, such as S = S, S = P, S = A, A = S, P = S, A = A, A = P, and P = A, within the combined clauses. The results of the research also show that Tamiang Malay exhibits a combination of accusative and ergative alignment patterns in its syntactic typology. In Tamiang Malay, the alignment pattern is primarily accusative, where the subject of an intransitive clause is marked the same way as the agent of a transitive clause, while the patient of a transitive clause is marked differently. However, Tamiang Malay also displays instances of ergative alignment that mark the subject of an intransitive clause the same way as the patient of a transitive clause, while the agent of a transitive clause is marked differently.